The Intersection of Gender, Media, And Policy: A Qualitative Analysis on Thai Newspaper Coverage of Women in Agriculture - Morgan A. Richardson Gilley; Richie Roberts; J. Joey Blackburn; Kristin Stair (Journal of International Agricultural and Extension Education, 2023)
Women empowerment and gender equality have been found to be statistically significant and positive predictors of global agricultural development. Therefore, reducing gender disparities can encourage economic progress and growth in developing nations. As such, determining effective ways to stimulate social progress and women’s empowerment has emerged as a critical need. One strategy used to raise the public’s consciousness about gendered issues in Thailand has been through mass media. In response, this study aimed to (1) determine to what extent Thailand’s newspaper coverage focused on topics related to women and the agricultural industry; and (2) describe how women in agriculture have been portrayed in newspaper coverage since the introduction of Thailand 4.0’s policy in 2016. Using a qualitative content analysis of Thailand’s newspaper coverage of women in the agricultural sector, four themes emerged: (1) economic policy implications for Thailand’s agricultural system; (2) human rights; (3) women entrepreneurship and leadership; and (4) agricultural development. Therefore, this study concluded that newspaper coverage of women in agriculture was diverse and conflicting – a finding not previously reported. The findings also revealed that women in agriculture have been underrepresented in newspaper publications historically. Moving forward, we provided critical implications for how future research, theory, and practice can depict women in agriculture more positively in the newspaper media.
Keywords: agricultural development; human rights; newspapers; policy; Thailand 4.0; women